Methodological framework for geodiversity application in geographic education from a case study of Canary Islands, Spain - Abramowicz, Dawid; Dóniz-Páez, Javier; Tritt, Remigiusz; Bąk, Mariusz (Quaestiones Geographicae, 2022)
The concept of geodiversity is becoming more widely used every year, beyond its contribution to the development of geotourism. It is estimated that geodiversity is as important as biodiversity in the functioning of Earth’s natural ecosystems. Therefore, an important problem is to recognize the possibilities on integrating geodiversity in geographic education, both formal and informal. The main aim of the study is to identify the subject of educating godiversity, included in the core curricula in Spain and Canary Islands and to identify the forms, didactic tools and methods of geodiversity education existed in selected national, natural parks and geoparks of Canary Islands. The study has shown that the application of geodiversity in educational practice is still unsettled.